Utilização da vitamina D e seus metabólitos na alimentação de frangos de corte - Garcia, Ana Flávia Quiles Marques (2012)
The aim of this study was to evaluate the effeet of different vitamin D metabolites on performance, bone quality characteristics, meat quaiity, immune response and intestine morphometrics of broiler chickens. There were used 952 1 -d-old chicks, male Cobb, distributed in a completely randomized design with four treatments, seven replications and 34 birds each. The treatments consisted in four different metabolites of vitamin D: D3, 25(OH) D3, 1.25(OH)2D3 and l a(OH)D3, providing 2000 and 1600 IU/kg feed of vitamin D in initial and growth period, respectively. The average weight, feed conversion and weight gain during the role period of production were worse in animals fed with lcL (OH) D3 when compared to other treatments (p<0.05). For bone diameters, bone resistance, seedor index, ash, calcium and phosphorus in the bone were not observed differences (p>O.05) between treatments. The meat color were different between treatments (p<O.05), but did not affect the meat quality. Ali metaboiites of vitamin D used in diets, except lcL(OH)D3 showed a good performance and bone quality, but influenced aspects of meat quality. The intestine weight differed between the treatments in 7, 21 and 42 days and the liver at 42 days of age. The other organs and immunological parameters (lymphoid organs, cutaneous basophil hypersensitivity reaction, macrophage activity assessment, measurement of nitric oxide and erythrocyte profile: leukocytes) were similar between the different metabolites. There was a significant effect (p<O.O5) of the vitamin D3 different metabolites on the villi length in jejunum and ileum at 7 days, between animals fed with 1 .25(OH) 2D3 and 1 ct(OH)D3 to the jejunum and 1,25(OH)2D3 and vitamin D3 to the ileum (p <0.05). The different sources of vitamin D affect the intestine morphometrics in the initial phase, but the effect was not observed in other phases. In conclusion, ail of the metabolites, except l,25(OH)D3 showed a good performance and similar bone quality, however the meat color and intestinal morphometrics differed between the different metabolites of vitamin D3 with the best results for the treatment 1,25(OH)2D3, although, the immunological parameters was similar between the different metabolites of vitamin D3.